Financing defence policy in the European Union in the context of the geopolitical situation - Katarzyna STABRYLA-CHUDZIO (Communications of International Proceedings, 2025)
Defence policy is an example of primarily national solutions limiting the effectiveness of the European Union. However, the European Commission's proposals for the new financial framework for 2028-2034 demonstrate not only an attempt to rationalize public expenditure but also an unprecedented response to the global geopolitical and socioeconomic situation. As a result, factors destabilizing the global economy are forcing EU institutions and Member States to take constructive action. The need to find a balance between the redistributive role of the EU budget and investments with significant European added value has already been reflected in the Next Generation EU and Security Action for Europe programs. The aim of this article is to answer the question of whether the Multiannual Financial Framework for 2028-2034 will change the spending structure, placing a greater emphasis on defence, and what the projected envelope for defence-related activities will be.
Keywords: defence policy; European Union finance; Multiannual Financial Framework 2028-2034; geopolitical situation.